(untitled) (ResearchJet Journal of Analysis and Inventions, 2021)
This article is devoted to the study of the peculiarities of the English proverbs and their relations to the human characteristics and evaluation. It also examines the process of linguistic conventionalization of the moral and legal sphere in relation to the concept of “Man” and its characteristics, which is the cognitive basis of this sphere, reveals the features of the linguistic representation of the moral and moral sphere of a person on the basis of proverbs and sayings of English.